The inflammatory architecture reflects the effects of pharmacological and genetic interventions on resolution of TLR2-mediated inflammation - Kramer, Clara; Pierre, Sandra; Zander, Nicole; Kolbinger, Anja; Aliraj, Blerina; Weigert, Andreas; Scholich, Klaus (Frontiers in immunology, 2025)
IntroductionImmune cells form defined pro- and anti-inflammatory regions around a pathogen during an innate immune response. These include, in Toll-like receptor (TLR)-2-induced inflammation, a core region containing the pathogen, an adjacent pro-inflammatory (PI) region and a surrounding anti-inflammatory (AI) region. Interventions targeting specific immune cells or signaling pathways disrupt this architecture and affect the resolution of inflammation. Here, we investigated, which changes in the inflammatory architecture may favor an increased resolution of inflammation. MethodsImmune cell networks and defined inflammatory regions were detected by high content imaging in an inflammation model induced by the TLR2 agonist zymosan. Resolution of inflammation was determined using thermal hypersensitivity.ResultsElimination of neutrophil recruitment using antibody depletion or GPR40-deficient mice had little effect on formation of the inflammatory structure or resolution of inflammation, as determined by the duration and strength of thermal hypersensitivity. High content imaging and FACS analysis showed that other phagocyting immune cells compensated for the loss of neutrophils in pathogen phagocytosis. In contrast, G2A-deficient mice, which exhibit enhanced resolution of zymosan-induced hypersensitivity, have reduced macrophage recruitment and polarization as well as a shift in the inflammatory architecture towards anti-inflammation. Importantly, the reduction of M1-like macrophage polarization without reduction of macrophage numbers by the JAK1/2 inhibitor baricitinib was not sufficient to alter the inflammatory structure or resolution of inflammation. DiscussionCombined with previously published results in the same inflammation model, we find that a strong decrease or increase of the PI region negatively affects resolution of inflammation, whereas a moderate decrease of 30-50% is associated with in part strongly enhanced resolution of TLR2-mediated inflammation.
Veröffentlicht: 17. Oktober 2025
Gesehen am 02.12.2025